Thu gọn biểu thức A=2x^2-5x-2x(x+1) B=(x+2y)(x-2y)-4y(x-y) C=(2x-8)(x^2+4x+16)-2x(x^2-2)

Question

Thu gọn biểu thức
A=2x^2-5x-2x(x+1)
B=(x+2y)(x-2y)-4y(x-y)
C=(2x-8)(x^2+4x+16)-2x(x^2-2)

in progress 0
Khánh Gia 1 year 2020-10-31T09:30:25+00:00 2 Answers 103 views 0

Answers ( )

    0
    2020-10-31T09:31:47+00:00

    A= 2x² – 5x – 2x( x + 1 )

    A= 2x² – 5x – 2x² – 2x

    A= -5x – 2x

    A= -7x

    B=( x + 2y )( x – 2y ) – 4y( x – y )

    B= x² – (2y)² – 4xy + 4y²

    B= x² – 4y² – 4xy + 4y²

    B= x² – 4xy

    C= ( 2x – 8 )( x²+ 4x + 16 ) – 2x( x² – 2 )

    C= 2x³ + 8x² + 32x – 8x² – 32x – 128 – 2x³ + 4x

    C= -128 + 4x

    CHÚC BẠN HC TỐT, CHO MIK XIN CTHN

     

    0
    2020-10-31T09:32:02+00:00

    Đáp án:

     

    Giải thích các bước giải:

    A = 2x^2 – 5x – 2x(x + 1)

    A = 2x^2 – 5x – 2x^2 – 2x

    A = -7x

    B = (x + 2y)(x – 2y) – 4y(x – y)

    B = x^2 – (2y)^2 – 4xy + 4y^2

    B = x^2 – 4y^2 – 4xy + 4y^2

    B = x^2 – 4xy 

    C = (2x – 8)(x^2 + 4x + 16) – 2x(x^2 – 2)

    C = 2(x – 4)(x^2 + 4x + 16) – 2x^3 + 4x

    C = 2(x^3 – 4^3) – 2x^3 + 4x

    C = 2(x^3 – 64) – 2x^3 + 4x

    C = 2x^3 – 128 – 2x^3 + 4x

    C = -128 + 4x

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )